Influencia del porcentaje de CaO orgánico sobre la permeabilidad, CBR y resistencia a la compresión inconfinada en un suelo CL - Gamboa López, Katherline Geraldine (2023)
The present investigation had as main objective to evaluate the influence of organic CaO, in the support capacity, resistance to unconfined compression and permeability index of soils susceptible to piping. Dosages of 0%, 1.5%, 3%, 4.5% and 6% of organic CaO calcined and sieved by 200 mesh were used. Soil characterization tests were carried out for classification purposes. Subsequently, the modified Proctor, CBR Index, resistance to unconfined compression and permeability tests were carried out in the soils with the different dosages of organic CaO. Finally, it was concluded that: organic CaO improved compaction, increasing its maximum dry density from 1.75 g/cm3 to 1.99 g/cm3 , that the CBR index increased from 8.54% to 57% at 100 MDS, and that the resistance to unconfined compression it increased from 1.1 g/cm2 to 3.4 g/cm2 . For all these properties, the highest value was obtained in those soil samples mixed with 4.5% organic CaO. Regarding the permeability index, it decreased to a minimum of 0.34 x 10 -6 cm/s.